THE FIRE RISK OF THE PLANT GROUPINGS WITH CISTUS IN THE AREA OF TLEMCEN (WESTERN ALGERIA) - Henaoui, Smain El-Amine; Bouazza, Mohammed; Amara, Mohamed (European Scientific Journal, ESJ, 2013)
Our paper focuses on the assessment of the sensitivity to fire Cistus plant groupings in the region of Tlemcen (Western Algeria). The study area consists mainly of Cistus, Pinus, Quercus and Tetraclinis considered the main species in the community. The bioclimatic analysis shows that the study sites tend towards certain aridity over time resulting in higher maximum temperatures and a wide dry period during the year, representing a major factor departures fires. The phytoecological analysis shows that the study area tends towards a certain therophytisation. Shrub and tree strata are the most vulnerable and flammable, for this reason, a number of species has been the subject of this study is to determine the time of flammability and combustibility depending on the water content. Testing flammability and combustibility of 38 plant species were used to classify species in ascending order according to their sensitivity to light, and draw a map of susceptibility to fires matorrals of Cistus aiming at the prevention and the fight against the devastating forest fires through different methods of planning.